2011
DOI: 10.1186/1477-7827-9-72
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression of serine protease inhibitors in bovine ovarian follicle: possible involvement in follicular growth and atresia

Abstract: BackgroundSERPINs (serine protease inhibitors) regulate proteases involving fibrinolysis, coagulation, inflammation, cell mobility, cellular differentiation and apoptosis. This study aimed to investigate differentially expressed genes of members of the SERPIN superfamily between healthy and atretic follicles using a combination of microarray and quantitative real-time PCR (QPCR) analysis. In addition, we further determined mRNA and protein localization of identified SERPINs in estradiol (E2)-active and E2-inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…2e, f). Approximately 37% of the DEgenes in the Uni-S vs Mul-S group and 41% in the Uni-L vs Mul-L group were reported to be associated with mammalian reproduction, such as TNFAIP6, MMP9, INSL3, LEPR, 3BHSD, LHCGR, ARL4C, CD36, CYP11A1, AMDHD1, SPOCK2, AMDHD1, MFAP5, CCL21, PTGFR, and SERPINA5 [23,[47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Of these genes, TNFAIP6, CYP11A1, CD36, PTGFR, and SER-PINA5 were found to be associated with the ovulation rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2e, f). Approximately 37% of the DEgenes in the Uni-S vs Mul-S group and 41% in the Uni-L vs Mul-L group were reported to be associated with mammalian reproduction, such as TNFAIP6, MMP9, INSL3, LEPR, 3BHSD, LHCGR, ARL4C, CD36, CYP11A1, AMDHD1, SPOCK2, AMDHD1, MFAP5, CCL21, PTGFR, and SERPINA5 [23,[47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Of these genes, TNFAIP6, CYP11A1, CD36, PTGFR, and SER-PINA5 were found to be associated with the ovulation rate.…”
Section: Discussionmentioning
confidence: 99%
“…In the GCs of periovulatory follicles of mice, the expression of PTGFR was shown to be drastically reduced [75].. Our results showed that PTGFR expression was downregulated in the large follicle from multiple goats, suggesting that the greater reduction of PTGFR expression observed in multiple goats may contribute to a the higher ovulation rate. Previous studies have reported that SERPINA5, a protease inhibitor, was expressed in the reproductive tract of adult mice and in the GCs of bovine follicles and that was highly expressed in bovine healthy follicles [60,76]. SERPINA5 expression was shown to be downregulated in ovarian cancer (OC) [77][78][79].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms and effects of complement speci c deregulation on tumor microenvironment are not clear. More works are needed to elucidate the complex process of cancer cells controlling complement activation and how complement affects tumor progression SERPING1 is also known as C1IH or CINH SERPING1 belongs to the serpins family of serine protease inhibitors, which regulate the proteases involved in brinolysis, coagulation, in ammation, cell migration, cell differentiation and apoptosis (Hayashi, Ushizawa et al 2011). Many studies have reported that the SERPING1 expression is up-regulated in tumors, including glioblastoma (Fornvik, Maddahi et al 2017), breast cancer and gastric cancer (Wojtukiewicz 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Our result showed that PTGFR gene was downregulated in large follicles from multiple goats, suggesting that the greater reduction of PTGFR gene expression in multiple goats may contribute to ovulate more. The previous studies reported that SERPINA5, as a protease inhibitor, was expressed in the reproductive tract of adult mice and in the GCs of bovine follicles, and was highly expressed in bovine healthy follicles [54,67]. SERPINA5 gene was down-regulated in ovarian cancer (OC) studies [68][69][70].…”
Section: Discussionmentioning
confidence: 99%